Historical dialectology in the digital age - Alcorn, Rhona; Kopaczyk, Joanna; Los, Bettelou; Molineaux, Benjamin J. (Benjamin Joseph), 1979- (Edinburgh University Press, 2019)
Drawing on the resources created by the Institute of Historical Dialectology at the University of Edinburgh this volume illustrates how traditional methods of historical dialectology can benefit from new methods of data-collection to test out theoretical and empirical claims